Parents’ Impression On Quality Of Children In Learning Process At Classroom - Dinda Salsabilah Siregar; Melina Putri Septiani Nasution; Thalya Marchanda Tarigan; Soechi Kurnia; Bambang Nur Alamsyah Lubis (Indonesian Counselor Association (IKI), 2023)
Parenting style referred to the approach and methods that parents used to raise their children. This research aims to explore parents' perceptions, policies and participation in supporting children's learning process. Descriptive qualitative was used as a research method. The data of this study was a result of questionnaire and interview, and the source of the data was taken from students at MIS AL-QUBA Medan. The result of this study was the role of parents did not influence student learning in class, due to a lack of supporting factors. Various studies show that parental involvement has a positive impact on children's academic achievement, social development and emotional well-being by some factors, communication between parents and students, nutritious food, and other supporting factors such as additional tutoring and learning facilities.